STRATEGI MENCIPTAKAN KEPUASAN KONSUMEN OJEK ONLINE GOJEK STUDI KASUS MAHASISWA UNIVERSITAS COKROAMINOTO YOGYAKARTA - Dedik Andri Purnomo; Muslich Pairan (Journal Competency of Business, 2019)
The purpose of this study is to determine the reliability, assurance, empathy can affect consumer satisfaction for Gojek for students of Cokroaminoto University Yogyakarta. The method used by the writer is survey research method. The method used in research conducted in direct observation of a symptom in a large or small population. Quantitative research is a research method that is descriptive in nature and uses more analysis, while quantitative research is research that intends to understand the phenomenon of what is experienced by research subjects in a holistic manner. Data collection methods used in this study were interviews and a list of questions. The types of data collected are primary and secondary. The data analysis technique used is quantitative analysis, which is data that can be measured in a numerical scale (numbers). The data analysis method used is qualitative analysis which consists of editing, coding, tabulating, quantitative analysis which consists of a reliability test, a validity test and a classic assumption deviation test. Based on the results of this study, the variables of reliability, assurance and empathy in online motorcycle taxi transportation are Fh> Ft or 25,383> 2.70 which means that Ho is rejected and Ha is accepted which means that it has a significant effect on customer satisfaction. And the more dominant influence on customer satisfaction is the assurance variable (assurance), namely 3.058